A Critical Survey on Renewable Energy Applications in the Philippines and China: Present Challenges and Perspectives - Li, Xin; Wang, Haizhi; Lu, Yuanru; Li, Wanlin (Frontiers in Energy Research, 2021)
China’s Belt and Road (B&R) initiative provides new ideas and opportunities for international cooperation. Renewable energy plays a crucial role not only in the national sustainable development framework of China and the Philippines but also in bilateral cooperation between them. However, some obstacles still need to be addressed because renewable energy cooperation between China and the Philippines has not been thoroughly and comprehensively studied to date. Based on an in-depth analysis of current renewable energy cooperation between China and the Philippines, this paper employs PESTEL analysis to fully investigate the cooperative advantages and disadvantages by considering politics (P), economy (E), society (S), technology (T), environment (E), and legislation (L) and proposes several constructive suggestions. The ultimate purpose was to design feasible schemes to ensure the sufficient utilization of renewable energy and the construction of integrated power grid systems to meet shortages of electricity supply especially in the isolated small islands in the Philippines through cooperation with China. In particular, it offers valuable advice concerning the U.S.-China trade war and COVID- 19 pandemic, outlining how cooperation in the exploitation of potential renewable energy is vital.